Mexican and U.S. anti-dumping and countervailing duty policies : issues in the free trade negotiations. - LONGLEY, Neil (1992)
Discusses current Mexican and US anti-dumping (AD) and countervailing policies and procedures. Compares trade remedy laws of the two countries, and examines major AD and CVD issues between them. Explores alternative methods in addressing these issues within a free trade agreement.